The conceptual scope of the definition of securities in the provisions of the Personal Income Tax Act of 26 July 1991, as an example of incorrect legal definition - Artur Halasz (Prawo Budżetowe Państwa i Samorządu, 2016)
The subject of this study is the analysis of the conceptual scope of the legal definition of securities in the provisions of the Personal Income Tax Act of 26 July 1991. The aim of the publication is to identify, following law analysis, that the definition of legal securities is an example of incorrect legal definition. The article goes on to point out the tax effects of this legal definition.